(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to identify the extent of the impact of non-Iraqi trading of shares in the Iraq Stock Exchange on the overall financial investment in the market size. And it imposes a search and no statistically significant relationship between variable trading non-Iraqis, the size and the total volume of the market and took the search Iraq Stock Exchange sample to search being the only private place to trade securities in Iraq for the period of 2009- 2015 in order to see if there is a positive impact on the size of trading non-Iraqis or not. Search and adopted the annual reports issued by the Iraq Stock Exchange the main conclusion are: Having a positive effect on the size of the trading of non-Iraqis in the financial volume of investment despite the presence of a sharp reduction in the size of the trading day. The recommendations of the research are: We aspire to be encouraging foreign investment in order to address the sharp decline in foreign investors trading in Iraq size and because of its importance to the level of the Iraqi economy as a whole and the particular market in is done by giving more features to the foreign investor or add other tools and means to encourage investment in Iraq.